Inside the Ring essays on Wagner's opera cycle (McFarland, 2006)
"Once tainted by association with Hitler and Nazism, Richard Wagner's work has experienced an international cultural renaissance in the last 25 years. This book, with essays for both the uninitiated and the seasoned fan, examines Wagner's Ring cycle from a wide array of modern perspectives"--Provided by publisher.